L'union économique et monétaire ouest africaine (UEMOA) : une nouvelle approche de l'intégration économique en Afrique de l'Ouest - Cissé, Mouhamadou Makhtar (Université Cheikh Anta Diop, 2014)
Keywords: Intégration économique; UEMOA; WAEMU

Regional Integration in Africa through the Harmonisation of Laws - Simo, Regis Yann (Regional Integration and Policy Challenges in Sub-Saharan Africa, 2014)
Domestic laws on the African continent have been considered inadequate to attract the investment needed for development and economic growth. A crucial catalyst in attracting investment on the continent is law reform. The formulation of legislation has twofold effects: firstly, it is perceived to mitigate the risks associated with doing business in Africa; secondly, it legally obligates African governments to comply with standards of protection accorded to international investors through the regulation of the business environment. The formulation of legislation is a key determinant of the quality of investment attracted to the continent. This Chapter assesses how the Organization for the Harmonization of African Business Law (OHADA) has contributed to regional integration and economic growth on the continent.
Keywords: Africa; Institutions; Law Reform; OHADA; Regional integration

Law and Development à L'Africaine: Evidence from the OHADA's Harmonization Process - Simo, Regis Yann (African Yearbook of International Law, 2014)
Until recently, doing business in developing countries, and in Sub-Saharan Africa in particular, was associated with high risk. Although each investment decision is associated with some risk, there are always obligations incumbent on host States in that regard. However, when domestic law is too obsolete to match the requirements of an evolving investment and commercial environment which it is supposed to regulate, and when its effects are unpredictable, one of the fundamental conditions for attracting investment goes missing. This eventually underscores the need for a legal reform. The phenomenon of 'globalisation' on the one hand, and the need for (developing) countries to integrate their economies into the global market, on the other hand, considerably accentuated the postulate of development through law.Against this background, some African countries, at the dawn of the 1990s, felt a need to 'modernise' their legal systems for the major part inherited from colonialism. In this vein, they entrusted a supranational organ, the OHADA, to perform that legal reform. This paper is an attempt to test the OHADA against the discourse of law as a development engine. Furthermore, this is an assessment of the extent to which OHADA, as a legal tool, could be useful in serving the purpose of regional integration and economic growth in Africa.
Keywords: Africa; Comparative Law; Law and Development; Law and economics; Law and finance; OHADA

Harmonising Public Procurement in the SADC - Harpe, Stephen de la (Journal of Law, Society and Development, 2014)
The promotion of international trade is seen as one of the important instruments to ensure development in developing nations and regions. The history of the World Trade Organisation (WTO) and the drafting of many regional and similar international trade agreements are evidence of this. The Southern African Development Community (SADC) is no exception.1 It is therefore strange that many states that are members of the WTO and actively encourage the opening up of international borders to free trade do not include public procurement2 in such free trade arrangements. This is particularly evident in developing states. If the WTO Government Procurement Agreement (GPA), which is a plurilateral agreement, is considered it is clear that many states do not wish to open their internal markets to competition in the public procurement sphere. It is therefore not surprising that public procurement has been described as the last rampart of state protectionism (Ky, 2012). Public procurement is an important segment of trade in any country (Arrowsmith & Davies, 1998). It is estimated that public procurement represents between 10% and 15% of the gross domestic product (GDP) of developed countries and up to 25% of GDP in developing states (Wittig, 1999). Unfortunately, governments often expect private industry to open up national markets for international competition but do not lead the way. Except for the limited use of pooled procurement,3 no specific provision is at present made for the harmonisation and integration of public procurement in the SADC. In view of the proximity of the member states, the interdependency of their economies and the benefits that can be derived from opening up their boundaries to regional competition in public procurement, the possibility of harmonisation and deeper integration in this sphere needs to be given more attention. The importance of public procurement in international trade and regional integration is twofold: first, it forms a substantial part of trade with the related economic and developmental implications; secondly, it is used by governments as an instrument to address socio-economic issues. Public procurement spending is also important because of its potential influence on human rights, including aspects such as the alleviation of poverty, the achievement of acceptable labour standards and environmental goals, and similar issues (McCrudden, 1999). In this article the need to harmonise public procurement in the SADC in order to open up public procurement to regional competition, some of the obstacles preventing this, and possible solutions are discussed. Reference is made to international instruments such as the United Nations Commission on International Trade Law (UNCITRAL), the Model Law on Public Procurement and the GPA. In particular, the progress made in the Common Market for Eastern and Southern Africa (COMESA) with regard to the harmonisation of public procurement, which was based on the Model Law, will be used to suggest possible solutions to the problem of harmonising public procurement in the SADC.

Political and Economic Integration in the SADC: Reforming the Energy Sector Regulatory System - Jobodwana, Z. Ntozintle (Journal of Law, Society and Development, 2014)
The Southern Africa Development Community (SADC), the African Union (AU) and other African regional economic communities (RECs) have as their ultimate objective the political and economic integration of the African continent. The SADC is home to a number of countries, all of them striving to improve their investment climate to attract foreign investors by reducing the costs of doing business in the region. One way of achieving this is by setting targets for and speeding up political and economic integration, improving interconnectivity and thereby enlarging the market size and enhancing its attractiveness. The SADC region still suffers from high levels of energy poverty through low access levels in all countries except South Africa and Mauritius. Numerous studies have shown that greater regional trading and cooperation on power development within the SADC could substantially reduce investment and operational costs as well as carbon emissions. The need for a regional power trading pool and regional cooperation grew out of the power utilities’ recognition of the vulnerability of individual countries if each continued to pursue a policy of self-sufficiency rather than out of a desire to minimise the social or financial costs of the region’s power. The power sector in southern Africa is undergoing tremendous reforms, more especially since the establishment of the Southern African Power Pool (SAPP) in August 1995. The SADC, however, faces serious challenges that include diminishing surplus generation capacity and the need to ensure that SADC citizens have equitable access to electricity at affordable prices. To meet these challenges, treaties and protocols have been adopted but are failing to deliver at the implementation stage. This article reviews the SADC energy-electricity regulatory framework in the context of economic and political integration and recommends the establishment of an independent regional regulatory authority to oversee the implementation of integrated holistic energy and air pollution control and prevention, and a common climate change policy. Such a regulator would be a highly resourced regional institution that will liaise with international institutions. This independent regional authority will serve as a catalyst for regional economic integration. It will also have a mandate to introduce and coordinate the establishment of an SADC regional emissions trading scheme that will contribute to managing the mitigation of greenhouse gases (GHGs) and the implementation of global warming adaptation strategies in the region.
Keywords: Climate change; Economic integration; Energy regulation; GHGs; Global warming; Political integration; Regional independent regulatory authority; SADC; SAPP; Treaty regime; UNFCCC

Harmonising the law of sale in the Southern African Development Community (SADC) : an analysis of selected models - Shumba, Tapiwa (Stellenbosch University, 2014)
It is generally recognised that diversity of laws may act as a barrier to the development of trade, both at international and regional level. In a globalised era, trade is necessary for economic development and ultimately for the alleviation of poverty. Although the WTO has done extensive work towards the removal of tariff barriers, there is also a need to focus on addressing non-tariff barriers which include legal barriers to trade. Institutionalised legal harmonisation at an international level has provided the necessary impetus for the development of harmonised laws in the area of international trade. The creation of regional economic communities within the purview of the WTO has also given rise to the necessity of legal harmonisation to facilitate intra-regional trade. A number of regional economic communities and organisations have noted legal harmonisation as one of their areas of regional cooperation. This study focuses on the need to harmonise the law of international sale within the SADC region in order to facilitate cross-border trade. The study points out that the harmonisation of sales laws in SADC is important for the facilitation of both inter-regional and intra-regional trade with the aim of fostering regional integration, economic development and alleviating poverty. Although the necessity of harmonising sales laws has been identified, no effort to this end exists currently in the SADC region. This study addresses the mechanisms by which such harmonisation could be achieved by analysing three models which have been selected for this purpose, namely the CISG, the OHADA and the proposed CESL. The main issues addressed include whether SADC Member States should adopt the CISG, join OHADA, emulate the CESL or should use any of the other instruments as a model for creating a harmonised sales law for SADC. In conclusion, it is observed that SADC has its own institutional and operational mechanisms that require a process and instrument tailor-made for the unique needs of the region. It is recommended that SADC should create its own common sales law based on the CISG but taking into account lessons learnt from both the OHADA system and the CESL. A number of legislative, institutional and operational transformative and reform mechanisms are recommended to enable the creation of such a community law and ensure its uniform application and interpretation.
Keywords: Africa; Economy; Foreign trade promotion; International unification; Mercantile law; Regional disparities; SADC; Southern African Development Community; Trade law

Diaspora, African Union and Sustainable Regional Integration in Africa - Asogwa, Felix; Didiugwu, Ifeanyi (African Journal of Politics and Administrative Studies, 2014)
The role of African Union in the African integration project has remained a topical issue among scholars. Various views have been canvassed on how to strengthen African Union for a more effective regional integration in Africa. This paper examined the central role the African Diasporas can play in repositioning African Union for a sustainable regional integration in Africa. Its analysis of the situation was anchored on the mo-functionalist integration framework and applied essentially the secondary data gathering techniques. Among other recommendations, it suggested for the creation of a pan-African Diaspora Organization.
Keywords: African; Diaspora; Regional integration

Globalization and Private International Law in Commonwealth Africa - Oppong, Richard (University of Arkansas at Little Rock Law Review, 2014)

Nuclear energy in Africa : a legal framework for sustainable energy access - Barnard, Michelle (North-West University, 2014)
The promotion of sustainable development is an objective shared by African Union (AU) member states and the pursuance thereof is expressly mandated by the Constitutive Act of the African Union, 2000 and the Treaty Establishing the African Economic Community, 1992. Lack of access to modern energy sources, such as electricity and the heavy reliance on traditional biomass as primary energy source are factors contributing to the non-achievement of the promotion of sustainable development. These factors are collectively referred to as energy poverty. The African Continent as a whole has limited, and in some instances, lack access to modern energy sources while the majority of its population relies heavily on traditional biomass as primary energy source. Africa can accordingly be classified as an energy poor region–a situation which does not bode well for the promotion of sustainable development. Access to reliable, affordable, economically viable, socially acceptable and environmentally sound energy services and resources is fundamental to socio-economic development. Mitigating the impacts of energy poverty and more specifically lack of access to modern energy sources on the sustainable development of Africa depends upon ensuring increased access to modern energy sources. The above-mentioned instruments furthermore contain provisions which link regional cooperation on the formulation of coordinated regional law and policy on areas/matters of common concern with the achievement of the objective of promoting sustainable development in Africa. One of the areas of common concerns listed is that of energy. Regional cooperation must accordingly be geared towards the effective development of the continent‘s energy and natural resources; promoting the development of new and renewable energy in the framework of the policy of diversification of sources of energy; and establishing an adequate mechanism of concerted action and coordination for the collective solution of the energy development problems within the AU. The formulation of coordinated energy law and policy should take place with reference to the specific sources of energy to be regulated. In this regard, the provisions of the Abuja Treaty and other sub-regional energy access initiatives list various sources of energy as forming part of a diversified AU energy mix – one of which is nuclear energy. In this study recommendations are made as to what should be embodied in a coordinated AU regional nuclear legal framework aimed at regulating increased access to nuclear energy capable of contributing towards the promotion of sustainable development. The recommendations are based on an examination of relevant international, regional and sub-regional legal instruments and other initiatives.
Keywords: African Union; Coordinated legal framework; Energy access; Energy poverty; Nuclear energy; Regional cooperation; Sustainable development

Sanitary and phytosanitary measures in the SADC region : a South African legal perspective - Joubert, Biandri (North-West University, 2014)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health within specified territories from the risks associated with the introduction and spread of pests and diseases through trade. The World Trade Organisation (WTO) developed an agreement on the application of SPS measures. South Africa is a member of both the WTO and the Southern African Development Community (SADC). In SADC, SPS measures are provided for in the SADC Sanitary and Phytosanitary Annexure to the Protocol on Trade of 1996. International Standard Setting Bodies (ISSBs) facilitate the effective application of the main elements of the relevant SPS agreements, especially harmonization and equivalence by establishing scientifically justified standards on which members may base their SPS measures. The relevant ISSB’s in terms of SPS measures are the OIE, IPPC and Codex Alimentarius. SPS measures have the potential to become or be used as non-tariff barriers to trade (NTBs). The SADC Protocol on Trade 1996 stipulates that policies and measures are to be implemented by members to eliminate existing forms of NTBs. Additionally members may not enforce new NTBs affecting or related to intra-SADC trade. The most relevant South African legislation in the context of SPS measures and this study is as follows: Agricultural Pests Act 36 of 1983, the Agricultural Products Act 119 of 1990; the Fertilizers, Farm Feeds, Agricultural Remedies and Stock Remedies Act 36 of 1947, the Liquor Products Act 60 of 1989, Meat Safety Act 40 of 2000, Foodstuffs, Cosmetics and Disinfectants Act 54 of 1972, Medicines and Related Substances Act 101 of 1965 and National Regulator for Compulsory Specifications Act 5 of 2008. The purpose of this study is to establish to what extent the South African legal framework complies with its obligations in terms of the SADC SPS Annexure to the Protocol on Trade.
Keywords: ISSB; NTB; SADC; SPS; Sanitary and phytosanitary measures; South Africa; WTO

La problématique de l’existence du droit communautaire africain: L’option entre mimétisme et spécificité - Kazadi Mpiana, Joseph (Revue libre de Droit, 2014)
Depuis la décennie 1990, une nouvelle génération des Organisations internationales africaines (OIA) émerge sur l’échiquier africain en s’inspirant, pour l’essentiel de son articulation normative et institutionnelle, du modèle européen d’intégration, notamment dans sa dimension communautaire tout en y apportant des spécificités africaines. Dès lors, le droit communautaire pose ses racines dans certaines OIA suscitant l’intérêt sans cesse nourri de la doctrine sur cette nouvelle matière. Mais existe-t-il vraiment un droit communautaire africain dont la doctrine s’efforce de présenter les grandes lignes, du moins de manière thématique ? La présente étude constitue une contribution à la problématique posée en envisageant de cerner la nature ainsi que les caractéristiques de ce droit qui se développe, principalement, en Afrique centrale et occidentale. Since the 1990s, a new generation of African International Organizations (AIO) emerges on the African continent, inspired, for most of its normative and institutional articulation, by the European model of integration, including its Community law while by bringing African specificities. Thus Community law is rooted in some AIO and the interest by the doctrine on this new branch is still constant. But is there really an African Community law that the doctrine seeks to systematize, at least thematically? This paper is a contribution to the problem posed by considering the nature and characteristics of this law developed mainly in Central and West Africa.

Legitimation of the economic community of West African states (ECOWAS): a normative and institutional inquiry - Nwankwo, Chidebe (Brunel University, 2014)
This thesis was submitted for the degree of Doctor of Philosophy and awarded by Brunel University LondonThis study is an attempt at determining the normative legitimacy of the Economic Community of West African States (ECOWAS). At its core, it scrutinizes the current mandate of the organization following the layering of economic integration objectives with human rights protection, sustenance of democracy, and the rule of law. The study discusses the elements of legitimacy across disciplines mainly, international law, international relations and political science. Legitimacy is eventually split along two divides, the normative and descriptive/sociological aspects. The study traces the normative content (shared/common values) underlying integration in Africa, concluding that integration has been born on new ideals such as human rights, democracy and the rule of law. Expectedly, Regional Economic Communities (RECs) as building blocks of the prospective African Economic Community (AEC) under the African Union (AU) regime are mandated to play a vital role in moving the continent forward upon these values. The inquiry is extended to the institutions of ECOWAS to determine their capacity to effectively implement the new mandate of the organization and operate supranationally. In the process, key legal and institutional shortcomings are discussed, particularly in relation to national institutions. It is argued that while human rights protection enhances the normative legitimacy of ECOWAS, it must not be pursued in isolation. Economic integration and protection of citizens’ rights are co-terminus and mutually reinforcing. Hence, community institutions must reflect this link if they are to be effective. The study concludes on the note that, while ECOWAS possesses layers of legitimacy, and have carried out legitimation steps, it cannot be considered a legitimate organization if Member States continue to be non-compliant with community objectives and if key legal questions remain unaddressed. It is submitted that ECOWAS is merely undergoing legitimation, whether it can eventually be considered a legitimate organization is dependent on addressing the identified challenges
Keywords: AU; Democracy; ECOWAS; Human Rights; Humanitarian Intervention; Legitimacy; Peace and Security; Regional integration

Direito comunitário material e integração sub-regional: contributo para o estudo das mutações no processo de integração económica e monetária na África Ocidental - Pereira, João Mendes (Universidade de Lisboa, 2014)
Pretende–se com esta tese intítulada “ Direito Comunitário material e Integração Sub–Regional: Contributo para o Estudo das Mutações no Processo da Integração Económica e Monetária da África Ocidental” pôr em evidência as mutações ocorridas na actual zona franco, no período colonial e pós colonial dos países africanos e as reformas das principais instituições comunitárias nela verificadas.Impõe–se uma nova abordagem da realidade contemporânea, no quadro das profundas mudanças ocorridas, a reclamar novos instrumentos de análise e de integração regional.Neste sentido, o Tratado da União Monetária Oeste Africana (UMOA) proclamou expressamente a vontade que animava os Estados–membros de prosseguirem na via da integração regional e de transformarem o conjunto das relações entre os si numa União Económica e Monetária.Com o propósito de somar à moeda única a harmonização legislativa, a abertura e a unificação dos mercados, a adopção de politicas económicas convergentes, propõe–se a União Económica e Monetária da África Ocidental (UEMOA) levar a cabo a habitual sequência da integração regional.Analisamos profundamente as políticas comunitárias, distinguindo primeiro políticas visando mais directamente a livre circulação das mercadorias, das pessoas, dos serviços e dos capitais no âmbito da UEMOA e da CEDEAO.A presente tese de doutoramento visa retratar o regime monetário regional que historicamente está ligado ao espaço colonial francês e depois se integrou progressivamente no sistema monetário internacional.Enfatizamos os principais instrumentos de política monetária regional, bem como o quadro institucional da União.Traçamos as premissas para uma teoria geral da integração dos Estados–membros da zona franco no contexto duma integração monetária e do novo multilateralismo comercial.Num ambiente cada vez mais concorrencial e difícil tornam-se prementes uma firme e necessária cooperação e integração regionais.No contexto da União Africana e da Nova Parceira para o Desenvolvimento do Continente Africano (NEPAD), evocamos as condições prévias do desenvolvimento com relação ao combate à pobreza. A nova Parceria Económica entre os países africanos e a União Europeia, consubstanciada no reforço do comércio internacional, permitindo robustecer as económicas africanas frágeis, que evidenciam falta de competitividade e de complementaridade, e uma um melhor inserção na económia regional e mundial.Nesta ordem de ideias, debruçamo-nos sobre as vantagens comparativas dos países da zona franco face às regras da Organização Mundial do Comércio (OMC).Partindo do entendimento de que o comércio internacional é necessário e que as trocas comerciais venham mesmo a ser inevitáveis, o que se propõe é uma nova discussão, inquirindo–se se o sistema multilateral de comércio pode fomentar e englobar um projecto de desenvolvimento. Intended with this designated thesis "Communitarian’ s Right material and Integration Sub - Regional: Contribute of Changes in the State Process of Economic Integration and Monetary Union of West Africa" to highlight the changes occurred in the actual franc zone during the colonial, post colonial countries African partners and major reforms of the main communitarian institutions been verified. It imposes - a new boarding of the contemporary reality, in the context of profound changes, to complain new instruments of analysis and regional integration. In this sense, the Treaty of West African Monetary Union (UMOA) expressly declared the will that animated the states members to proceeded the path of regional integration and to transform the set of relations between States in their economic and monetary union. In order to add the single currency legislative harmonization, unification and the opening market, the adoption of economic policies converge, it is proposed to Economic and Monetary Union of West Africa (UEMOA) the habitual sequence of regional integration. We deeply analysed the politics communitarian, distinguishing first politics aiming at more directly the free movement of goods, people, services and capitals in the scope of the UEMOA and the CEDEAO. This doctoral thesis aims to portray the regional monetary regime is historically linked to the French colonial space, after it was progressively integrated into the International monetary system. We set the foundations for a general theory of integration of states - members of the franc zone in a context of monetary integration and the new multilateral trade. We followed the assumptions for a general theory of integration of states - members of the franc zone in a context of monetary integration and the new commercial multilateralism. 6 In an increasingly competitive and difficult to become a strong and urgent need for cooperation and integration regional’s. In the context of the African Union and New Partnership for the Development of Africa (NEPAD) evoke the preconditions of development in relation to combat poverty. Having in account the new Economic Partnership between the countries and consubstantial in the reinforcement of the international trade for the fragile African economics, evidencing lack of competitiveness and complementarily with sight to one better insertion in the regional and world-wide economic. In this order of idea, concentrating on the comparative advantages and more favourable to the franc zone countries over the rules of the World Trade Organization (WTO). From understanding that international trade is necessary and that trade may even be inevitable, what is proposed is a new thread, asking if the multilateral trading system can promote and incorporate a development project.
Keywords: African Union; Communitarian Right; Comércio; Democracia; Democracy; Desenvolvimento; Development; Direito Comunitário; Estado; Franc zone; Globalization; Globalização; Integração regional; Pan Africanism; Panafricanismo; Regional integration; State; Trade; União africana; Zona franco

Integração na África Austral : a comunidade para o desenvolvimento da África Austral (SADC) e os condicionantes históricos e políticos da integração - Xavier, Nathaly Silva (Universidade Federal do Rio Grande do Sul, 2014)
A Comunidade para o Desenvolvimento da África Austral (SADC) é um dos principais processos de integração regional da África. A criação da Comunidade está fundada no processo de descolonização da África Austral e na mobilização dos Estados da Linha de Frente na contenção das políticas de desestabilização da África do Sul durante o período do apartheid. A concepção de regionalismo desenvolvimentista, na qual os processos de integração regionais têm objetivos mais amplos do que os meramente comerciais, vai ao encontro da realidade da África Austral. O conceito de comunidade de segurança também é útil para compreender as relações regionais que envolvem a criação e o desenvolvimento da SADC ao longo das décadas, tendo em vista a sua atuação também nas questões securitárias. O objetivo desse trabalho é analisar a evolução da SADC, desde a sua criação até os anos 2000, enfatizando os aspectos históricos e políticos desse processo. Parte-se do pressuposto de que há uma forte relação entre segurança, desenvolvimento, paz e integração e que não há como a integração econômica aprofundar-se em um contexto de instabilidade político-securitária regional. The Community for the Southern African Development Community (SADC) is one of the main regional integration processes in Africa. The creation of the Community has its origins in the process of decolonization in Southern Africa and in the Front Line States the mobilization to contain the destabilization policies by South Africa during the apartheid period. The concept of developmental regionalism, in which the processes of regional integration have broader objectives than purely commercial, folows the reality of Southern Africa. The concept of security community is also useful for understanding regional relations involving the creation and development of SADC over the decades, concerning your activity also in security issues. The aim of this study is to analyze the evolution of SADC since its creation until the 2000’s, emphasizing the historical and political aspects of this process. It adopts the assumption that there is a strong relationship between security, development, integration and peace and there is no way to deepen economic integration in a context of regional political and security instability. La Communauté de Développement de l'Afrique Australe est l'un des principaux processus d'intégration régionale en Afrique . La création de la Communauté est fondée dans le processus de décolonisation en Afrique australe et dans la mobilisation de les État du Linge de Front pour contenir les politiques de déstabilisation de l'Afrique du Sud au cours de la période de l'apartheid. Le concept de régionalisme développementiste, dans lequel les processus d'intégration régionale ont des objectifs plus larges que purement commerciale, répond à la réalité de l'Afrique Australe . Le concept de communauté de sécurité est également utile pour comprendre les relations régionales sur la création et le développement de la SADC au cours des décennies , en vue de ses performances aussi dans les questions sécuritaire . L’objectif de cette étude est d'analyser l'évolution de la SADC depuis sa création jusqu'aux années 2000 , mettant l'accent sur les aspects historiques et politiques de ce processus . Séjours à l'hypothèse selon laquelle il existe une relation forte entre la sécurité, le développement, l'intégration et la paix et il n'ya aucun moyen d'approfondir l'intégration économique dans un contexte d’instabilité politique et securitaire régionale.
Keywords: Afrique Australe; Comunidade para o Desenvolvimento da África Austral; História; Integration; Integração regional; Política; Relações internacionais; SADC; Southern Africa; África